Reconfigurable Microstrip Double-Dipole Antennas for Personal Wireless Communications - Eldek, Abdelnasser; Abdallah, Abubaker; Manzoul, Mahmoud (Scientific Research Publishing, 2011)
In this paper, a number of reconfigurable antennas are designed to support multiband and wideband wireless applications in different frequency bands in the range between 1 GHz and 6 GHz. The proposed designs consist of microstrip-fed two dipoles through simplified balun. By controlling the lengths of the dipoles by connecting or disconnecting slots, we are able to change the antenna operating frequency as well as the operation mode. Two modes are supported by all of the proposed antennas: Multiband and Broadband modes.
Keywords: Reconfigurable Antennas; Dipole; Wideband; Multiband